Critical factors of an integrated approach to the economics of small modular reactors - Smirnova, L. S.; Korolev, S. A. (Atomic energy (New York, N.Y.), 2024)
Conventional economic assessments of nuclear power plant projects include a standard set of design technical and economic characteristics using established methods of economic and investment analysis. Evaluating innovative projects of small modular reactors (SMRs) should account for additional factors related to the specifics of projects, their purpose and territorial location, features of operating modes, optimal project capacity for a specific scenario, etc. Additional factors make project economic estimates more realistic. The article examines critical aspects and factors capable of affecting the economic performance of SMR projects operating in different market niches. Moreover, the article touches upon issues related to the risks of implementing these projects. SMR projects are implemented under external conditions complementing the technical and economic assessments of power plant projects. These conditions include scenario factors, site conditions, regulatory aspects, design requirements, as well as organizational, financial, and market mechanisms. The concept of extended analysis in performing economic assessments of innovative SMR projects is urgent due to their various practical applications.